(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
This article develops an integrated electrochemical technology for industrial wastewater treatment based on electrocoagulation, electroflotation, and electrooxidation. The concept is built on mechanistic complementarity: electrocoagulation generates metal hydroxide coagulants in situ to destabilize colloids, emulsions, and dissolved metals; electroflotation intensifies solid liquid separation through fine gas bubbles that rapidly lift and remove formed flocs; electrooxidation then targets the residual dissolved and refractory organic fraction to improve final effluent quality for discharge or reuse